Historiography and problematization on the 'polis' and the politics of the Athenians - Virgolino, Mariana Figueiredo (Romanitas - Revista de Estudos Grecolatinos, 2016)
Review of: MORALES, F. A. A democracia ateniense pelo avesso: os metecos e a política de Lísias. São Paulo: Edusp, 2014. 392 p.
Keywords: Classical Greece; Polis; Democracy